Clique vintage culture flower shop - Abdullah, Alya Jazmine; Mohamed Fauzi, Nur Adila; Ibrahim, Nursyuhada; Rozalli, Nor Shahirah; Mansul, Masliza (2021)
The Clique Vintage Culture Flower Shop is a new business that sells many kinds of flower and bouquet with the tagline “Our Flowers Create Emotions” so that it can create a positive and memorable tagline that sticks in the customer’s head. The form of this business is a new partnership business which is established on 15 September 2021. The type of this business is in a floral industry and the main activity is specialized in selling and arrangement of flowers. The owner of this business includes the General Manager, the Administration Manager, the Marketing Manager, the Operation Manager and the Financial Manager which will manage this business. Moreover, this business capital is amounted to RM162,482 which is borrowed from bank as a loan and a few from personal cash. Clique Vintage Culture Flower Shop is a business that sells many kinds of artificial and dried flowers that is operating in Malaysia. We choose this business name because it is unique and it is easy for the people to pronounce and remember. The reason that we want to set up this kind of business is because of our love and passion towards flowers and we want to share it with other people too so that it can make their day. This business will be selling flowers at a more affordable price for all people especially to the people who loves flower. The product and services that this business offered besides selling and arrangement of flower, is also custom design for flowers. So, the customers can customise their flowers according to their preference. So, this business will offer a unique arrangement of flowers for the customers and it is different from other flower shop. The location of this business will be located at D6, 03-04, Persiaran Multimedia, Tamarind Square, 63000 Cyberjaya, Selangor. The reason for choosing this location is because it is a strategic place that led to a less competition that can attract many people such as flower lovers, partners and so on. So, Clique Vintage Culture Flower Shop business has a bright future in the upcoming years.